NOTES ON HISTORY AND MEMORY THROUGH IMAGES - Navarro Fuentes, Carlos Alberto (2022)
The aim of the essay is to propose the relationship that the image maintains withhistory and memory as forms of approach to the past. The methodology consisted ofreviewing the way in which the historical discipline - and other social sciences - hasused the image as a tool to study social worlds, identifying advances and limitations inthis matter, concluding that it has a fundamental role in the configuration processes ofcollective memory, especially where traumatic experiences have taken place.